Antimicrobial activity and cytotoxicity study of cerium oxide nanoparticles with two different sizes. Issue 4 (24th November 2022) - Yefimova, Svetlana; Klochkov, Vladimir; Kavok, Nataliya; Tkachenko, Anton; Onishchenko, Anatolii; Chumachenko, Tatyana; Dizge, Nadir; Özdemir, Sadin; Gonca, Serpil; Ocakoglu, Kasim
Abstract: The control over bacterial diseases requires the development of novel antibacterial agents. The use of antibacterial nanomedicines is one of the strategies to tackle antibiotic resistance. The study was designed to assess the antimicrobial activity of cerium oxide (CeO2 ) nanoparticles (NP) of two different sizes (CeO2 NP1 [1–2 nm] and CeO2 NP2 [10–12 nm]) and their cytotoxicity towards eukaryotic cells. The antimicrobial activity, effects of nanoparticles on DNA cleavage, microbial cell viability, and biofilm formation inhibition were analyzed. The impact of cerium oxide nanoparticles on eryptosis of erythrocytes was estimated using annexin V staining by flow cytometry. The newly synthesized CeO2 NP1 and CeO2 NP2 displayed moderate antimicrobial activities. CeO2 NP1 and CeO2 NP2 exhibited single‐strand DNA cleavage ability. CeO2 NPs were found to show 100% microbial cell viability inhibition at a concentration of 500 mg/L. In addition, CeO2 NP1 and CeO2 NP2 inhibited the biofilm formation of S. aureus and P. aeruginosa . Larger cerium oxide nanoparticles were found to be less toxic against erythrocytes compared with the smaller ones. CeO2 nanoparticles demonstrate moderate antimicrobial activity and low cytotoxicity towards erythrocytes, which make them promising antibacterial agents.